Upaya Peningkatan Hasil Belajar Matematika Materi Mengenal Pecahan Sederhana Melalui Metode Demonstrasi Menggunakan Media Manipulatif - Abi Kusno (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
The purpose of this research was to improve the learning outcomes of class II students at Ta'mirul Islam Elementary School, Surakarta in learning Mathematics, teaching material to recognize simple fractions using the demonstration method using manipulative objects. This research is classroom action research with the number of students consisting of 13 male students and 13 female students. Data collection techniques in this research include tests, observation and documentation. This research action consists of two cycles, each cycle consisting of planning, taking action, observing action, and reflecting. The results of this research show that the average student learning outcomes from the pre-cycle were 71 with learning completeness of 38%. These learning outcomes are still below the KKM determined by the school. In cycle I, the average score was 82 with a learning completeness of 77%, in cycle II the average score was 92 with a learning completeness of 100%. The results of this research show that learning using demonstration methods through folded paper manipulative media can improve student learning outcomes.